Growing pains? Change in the New Zealand childcare market 2006–2016 - Gallagher A (Massey University)
There has been a significant growth in childcare in New Zealand (NZ) since 2006. Shaped by debates around the marketisation of childcare, this paper will make some key observations about the NZ childcare market. I will argue that the landscape of childcare has changed in favour of a burgeoning private sector and consider the recent impetus for corporatisation. Finally, I will examine the discourse of parental ‘choice’ which pervades policy discussions around ECE in New Zealand and how this plays out in the face of an expanding private for-profit sector.
Keywords: childcare; marketisation; parent consumer; private sector; 0406 Physical Geography and Environmental Geoscience; 1302 Curriculum and Pedagogy; 1604 Human Geography